Performance of front bumper and hood system with pedestrian safety subjected to frontal impacts - Jalaluddin, Mai Nursherida (2011)
A performance of front bumper and hood system with pedestrian safety subjected to A performance of front bumper and hood system with pedestrian safety subjected to frontal impacts is presented and discussed in this project. The aim of this study is to analyze the effect of steel, aluminum and composite material on energy absorption and pedestrian safety of automotive front bumper system and hood. The front bumper beams and hood made of e-glass/epoxy composite and carbon epoxy composite are studied and characterized by impact modeling using LS-DYNA V971, according to United States New Car Assessment Program (US-NCAP) frontal impact velocity and based on European Enhanced Vehicle-safety Committee. The most important variable of this structure are mass, material, head injury criteria, leg injury criteria and Specific Energy Absorption (SEA). The results are compared with bumper beam and hood made of mild steel. Three types of materials are used in the present study which consists of mild steel as references material, Aluminum AA5182, E-glass/epoxy composite and carbon fiber/epoxy composite with three different fiber orientations [0o/60o]S, [0o/30o/60o]S and [0o/30o/60o/90o]S. frontal impacts is presented and discussed in this project. The aim of this study is to analyze the effect of steel, aluminum and composite material on energy absorption and pedestrian safety of automotive front bumper system and hood. The front bumper beams and hood made of e-glass/epoxy composite and carbon epoxy composite are studied and characterized by impact modeling using LS-DYNA V971,according to United States New Car Assessment Program (US-NCAP) frontal impact velocity and based on European Enhanced Vehicle-safety Committee. The most important variable of this structure are mass, material, head injury criteria,leg injury criteria and Specific Energy Absorption (SEA). The results are compared with bumper beam and hood made of mild steel. Three types of materials are used in the present study which consists of mild steel as references material, Aluminum AA5182, E-glass/epoxy composite and carbon fiber/epoxy composite with three different fiber orientations [0o/60o]S, [0o/30o/60o]S and [0o/30o/60o/90o]S. The beams were subjected to impact loading to determine the internal energy and SEA. The in-plane failure behaviors of the composites were evaluated by using Tsai Wu failure criterion. The results for the composite beams are compared to that of the reference beam to find the best material with highest SEA. LS-DYNA Finite Element Analysis software was used. The results showed that carbon fiber/epoxy composite bumper can reduce the bumper mass and has the highest value of SEA followed by glass fiber/epoxy composite, aluminum AA5182 and mild steel. For the pedestrian safety, the dummy was subjected to frontal impact to determine the head injury criteria. The results for the composite materials and aluminum AA5182 are compared to that of the reference material to find the best material with lowest value of Head Injury Criterion (HIC). The results showed that aluminum AA5182 with thickness 1.0 mm hood has the lowest HIC value with 549.70 for HIC15 and 883.00 for HIC36 followed by mild steel with 657.40 for HIC15 and 980.90 for HIC36, glass fiber/epoxy composite with 639.60 for HIC15 and 921.70 for HIC36 and carbon fiber/epoxy composite bumper with 1197.00 for HIC15 and 1424.00 for HIC36. From the present work, the carbon glass fiber/epoxy bumper beams and aluminum AA5182 hood are proposed since it met the European New Car Assessment Programme (N-CAP) criteria. For Leg Injury criteria determination, the legform model was used to stimulate accidents against the front of the car. The European New Car Assessment Program (NCAP) parameter was used to simulate accidents involving pedestrian impact at 40km/h, where dummy models or legform served as impactors. For legform simulation results, the tibia acceleration 91.5 g, 4.2 mm shear displacement and 12.0˚ bending angle graphs are below the regulation limit. It is because there are no contact between the front bumper beam and the legform, so that the injury is less. This is shows that the clearance between the bumper shell and front bumper beam are enough. The appropriate value is 75 mm. As a conclusion, the minimum clearance between the leg and the bumper.